Design of Solar Home Charging for Individual Electric Vehicles: Case Study for Indonesian Household - Nurwidiana, Nurwidiana; Nugroho, Dedi; Fatmawati, Wiwiek (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
This study aims to examine the use of solar energy through Rooftop Photovoltaic (RPV) technology for solar-powered home charging of individual electric vehicles (EVs) in Indonesia. Simulations using HOMER Pro software are carried out to analyze both the energy and financial performance of the designed RPV system. According to the calculations, a 4 kW RPV system is required to meet the daily energy demand for EVs in the household sector. The off-grid RPV system design consists of 12 unit 325 wp PV panels, 36 units of 100AH battery as power storage, and a 4000-watt inverter to convert DC from RPV system into AC for battery charging. Simulation results from HOMER Pro software confirm that the designed RPV system can adequately supply the electricity needed for home charging, generating a total of 6449 Wh per year. With an annual energy consumption of approximately 4,190 kWh/year, the proposed system not only meets the daily energy needs of EVs but also provides excess power to be used by additional electrical equipment. Additionally, the proposed system can reduce 77.89 tons of CO2 emissions over the 25-year project lifespan.